The influence of the perinatal chronic hyperglycaemia on the pattern of NOS isoforms expression in left ventricle myocardium in male rats of pre-pubertal age - O. V. Gancheva; Yu. M. Kolesnyk; Yu. I. Vorodeeva (Patologìâ)
The aim of our study was to find out the features of the nitric oxide synthase (NOS) isoforms expression in longitudinal and transversal layers of the myocardium of the left ventricle in male rats of 3 months, which are descendants of female rats with experimental gestational diabetes (EGD).